2008
DOI: 10.1016/j.brat.2008.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Rumination and worrying as possible mediators in the relation between neuroticism and symptoms of depression and anxiety in clinically depressed individuals

Abstract: Rumination and worrying are considered possible mediating variables that may explain the relation between neuroticism and symptoms of depression and anxiety. The current study sought to examine the mediational effects of rumination and worry in the relationships between neuroticism and symptoms of depression and anxiety in a sample of clinically depressed individuals (N=198). All patients completed a battery of questionnaires including measures of neuroticism, rumination, worrying, depression, and anxiety. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
137
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(163 citation statements)
references
References 53 publications
(61 reference statements)
21
137
1
4
Order By: Relevance
“…The effect of condition on patient valence is represented by weight a, whereas weight b is the effect of patient valence on pain, partialling out the effect of condition [25]. The total effect (c) of condition upon pain consists of both the direct (c') and the indirect (ab) effect.…”
Section: Pain -Accepted Uncorrected Manuscriptmentioning
confidence: 99%
“…The effect of condition on patient valence is represented by weight a, whereas weight b is the effect of patient valence on pain, partialling out the effect of condition [25]. The total effect (c) of condition upon pain consists of both the direct (c') and the indirect (ab) effect.…”
Section: Pain -Accepted Uncorrected Manuscriptmentioning
confidence: 99%
“…By reflecting on the literature and considering the fact that transdiagnostic factors of perfectionism and RNT are caused by the individual's illogical beliefs (22,23), the current study indicated a correlation between perfectionism and RNT and also a significant relationship between these two transdiagnostic factors and anxiety. It appears that these two factors can predict anxiety symptoms.…”
Section: Objectivesmentioning
confidence: 75%
“…Roberts, Gilboa and Gotlib (1998) have suggested that as individuals high in neuroticism tend to focus on their dysphoric experiences, perseverative cognition may be the most frequent cognitive manifestation of this personality trait. In fact, perseverative cognition may be the pathway through which neuroticism impairs psychological health (Barnhofer & Chittka, 2010;Muris et al, 2005;Nolan et al, 1998;Roberts et al, 1998;Roelofs et al, 2008). Robinson (2007) suggested that the relationship between neuroticism and perseverative cognition is based on a difference in executive cognitive function.…”
Section: Theoretical Perspectives On Neuroticismmentioning
confidence: 99%
“…This condition drains cognitive and emotional energy as they promote prolonged activation of psychological stressors during respite periods (Brosschot, Pieper, & Thayer, 2005). This prolonged activation may eventually lead to health problems such as cardiovascular disorders and depression (Brosschot et al, 2005;Nepon, Flett, Hewitt, & Molnar, 2011;Nolan, Roberts, & Gotlib, 1998;Roelofs, Huibers, Peeters, Arntz, & van Os, 2008). To prevent these, it is important to find concrete coping strategies that workers can use to reduce WPC on a daily basis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation